CONSUMPTION RATIONALITY OF STUDENTS IN THE FACULTY OF ECONOMICS UNIVERSITAS NEGERI MALANG VIEWED FROM LOCUS OF CONTROL MEDIATED BY FINANCIAL LITERACY - Novita Ika Fitriani; Sri Umi Mintarti Widjaja; Wening Patmi Rahayu (Yayasan Education and Social Center, 2021)
This study aims to determine the consumption rationality of Faculty of Economics students, Negeri Negeri Malang, regarding locus of control mediated by financial literacy. In this study, the financial literacy variable, apart from being used as an independent variable, is also used as a mediating variable that can bridge the relationship between variables. This study uses a quantitative approach to causality by using path analysis techniques. This study uses a quantitative approach to causality by using path analysis techniques. The sample in this study amounted to 273 respondents consisting of Faculty of Economics students, Negeri Negeri Malang class 2017. The sampling technique used a proportional random sampling technique, which is a random sampling technique that is balanced or proportional to the number of subjects. Data collection techniques with questionnaires and documentation. The results of this study indicate that there is a direct influence of locus of control on financial literacy and consumption rationality. There is a direct influence of financial literacy on consumption rationality. The path coefficient value on the direct influence is greater than the indirect effect on the locus of control on consumption rationality, so financial literacy does not act as a mediation on the influence of locus of control on consumption rationality. Suggestions for further research are to examine other variables and use different analytical tools so that more detailed results are obtained